Analisis Pengendalian Kualitas Produk Arabica Roasted Coffee Beans Pada Drama Coffee Roastery - Shofa Zahrah, Saffaana; Tjondro Winarno, Sri; Hafi Idhoh Fitriana, Nisa (Forum Agribisnis, 2025)
The unique aroma of arabica coffee beans will come out after passing through the roasting step, therefore the quality control is important. Quality control in the company is very important to produce products that have a slick quality value so consumers had their own satisfaction when buying products. This study aims to analyze (1) The level of product defects of arabica roasted coffee beans (2) The level of process stability and processing capacity of arabica roasted coffee beans products in achieving zero defects (3) Quality improvement efforts to minimize product defects of arabica roasted coffee beans. The sample used in this study was 100 samples of arabica roasted coffee beans products using non-probability sampling techniques due to the limited time and cost of the study in drawing random probability samples. This research was conducted at Drama Coffee Roastery, Pasar Tunjungan, first floor Unit 08, Jalan Tunjungan 88, Surabaya City which had wide marketing of arabica roasted coffee beans products, covering Surabaya area or outside the city, and has a product license and legality. The method used in this research was six sigma method with DMAIC (Define, Measure, Analyze, Improvement, and Control) approach. The results showed that Drama Coffee Roastery had 4 types of defects product, was overdeveloped, underdeveloped, cracked, and striped. Drama Coffee Roastery had a sigma level value of 3.35 which explains that UMKM Drama Coffee Roastery had the ability to process product quality within the scope of the average industry in Indonesia. This indicates that the product requires quality control to achieve zero defects in order to entry international coffee market. The study found that six sigma method was effective in solved problems that occur at Drama Coffee Roastery by reviewing green beans, green beans roasting time, sorting improvements, and green beans storage improvements that will have an impact on the supply chain efficiency of arabica roasted coffee beans products.